2011
DOI: 10.1074/jbc.m110.178640
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Enrichment of Vitamin A at the C20 Position Slows the Formation of Detrimental Vitamin A Dimers in Wild-type Rodents

Abstract: Degenerative eye diseases are the most common causes of untreatable blindness. Accumulation of lipofuscin (granular deposits) in the retinal pigment epithelium (RPE) is a hallmark of major degenerative eye diseases such as Stargardt disease, Best disease, and age-related macular degeneration. The intrinsic reactivity of vitamin A leads to its dimerization and to the formation of pigments such as A2E, and is believed to play a key role in the formation of ocular lipofuscin. We sought a clinically pragmatic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 42 publications
2
65
0
1
Order By: Relevance
“…Similar to humans, Abca4 knockout (Abca4 −/− ) mice exhibit increased rates of vitamin A dimerization and lipofuscin accumulation compared with their wild-type counterparts (17,18). Administration of C20-D 3 -vitamin A has been shown to inhibit vitamin A dimerization (19). Thus, to determine whether vitamin A dimerization was responsible for RPE lipofuscin formation, we administered a standard rodent diet to a cohort of Abca4 −/− mice (control group) and compared signatures of retinal health with another cohort, in which we replaced vitamin A in the standard diet by the same amount of C20-D 3 -vitamin A (treatment group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to humans, Abca4 knockout (Abca4 −/− ) mice exhibit increased rates of vitamin A dimerization and lipofuscin accumulation compared with their wild-type counterparts (17,18). Administration of C20-D 3 -vitamin A has been shown to inhibit vitamin A dimerization (19). Thus, to determine whether vitamin A dimerization was responsible for RPE lipofuscin formation, we administered a standard rodent diet to a cohort of Abca4 −/− mice (control group) and compared signatures of retinal health with another cohort, in which we replaced vitamin A in the standard diet by the same amount of C20-D 3 -vitamin A (treatment group).…”
Section: Resultsmentioning
confidence: 99%
“…As lipofuscin accumulation is a hallmark of RPE senescence, this work suggests that vitamin A dimerization is a major chemical event responsible for RPE senescence and that inhibiting dimerization may impede RPE senescence and related retinopathies. C20-D 3 -vitamin A slows the rate of vitamin A dimerization by as much as sevenfold in test tubes (19), and the rate of accumulation of orange ocular pigments and A2E by four-to sixfold in animals, but does not entirely halt the dimerization. As such, the remaining lipofuscin may result from residual dimerization of vitamin A or from other, poorly understood events that may also be responsible for lipofuscinogenesis in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Replacing the C20 hydrogen atoms of vitamin A with deuterium atoms (i.e. C20-D 3 -vitamin A) makes this bond harder to cleave and impedes vitamin A dimerization (14). In this study we sought to determine whether retarding the intrinsic reactivity of vitamin A to dimerize could slow lipofuscin formation in the RPE and delay changes associated with human Stargardt disease.…”
mentioning
confidence: 99%
“…In the accompanying article, we have shown that the ratedetermining step in vitamin A dimerization is the cleavage of a C20 carbon-hydrogen bond of the retinaldehyde-PE Schiff base (14). Replacing the C20 hydrogen atoms of vitamin A with deuterium atoms (i.e.…”
mentioning
confidence: 99%
“…Recruitment is now ongoing for a phase 2 placebocontrolled study (ClinicalTrials.gov identifier: NCT02402660) that will examine tolerability and effects of ALK-001 in STGD1. As indicated by the authors, the efficiency with which native vitamin A is replaced by C20-D 3 -vitamin A remains to be determined (55). An increase in total vitamin A intake might also potentiate the drive toward bisretinoid formation (56).…”
Section: Therapeutic Approaches That Target Bisretinoid: Clinical Andmentioning
confidence: 99%